The Influence of Communication, Leadership, and Budget Management on Project Success - Gunawan, Adriani; Kumala, Destiana; Eryandi, Eryandi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
This article examines the influence of communication, leadership, and budget management on project success. Project success is often determined by internal factors that play a crucial role in achieving project objectives. The study employs a qualitative approach to understand the relationships between these three variables in project management contexts. Through in-depth interviews with project managers and team members involved in various projects across several industries, the findings highlight that effective communication among team members and stakeholders is vital in ensuring projects are executed as planned. Additionally, adaptive leadership styles and the project manager's ability to manage the budget wisely were also identified as key factors contributing to project success. The article concludes that the integration of these three elements—communication, leadership, and budget management—are essential in determining the success of a project. This research provides valuable insights for professionals and project management practitioners to enhance their approaches to project management in order to achieve optimal outcomes.